2015
DOI: 10.1080/0964704x.2015.1070249
|View full text |Cite
|
Sign up to set email alerts
|

Vincenzo Neri and His Legacy in Paris and Bologna

Abstract: Italian neurologist Vincenzo Neri was able to discover cinematography at the beginning of his career, when in 1908 he went to Paris to learn and improve his clinical background by following neurological cases at La Pitié with Joseph Babinski, who became his teacher and friend. While in Paris, Neri photographed and filmed several patients of famous neurologists, such as Babinski and Pierre Marie. His stills were published in several important French neurological journals and medical texts. He also collaborated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…As Federico Vanone, Lorenzo Lorusso, and Simone Venturini have pointed out, Neri's mode of working demonstrated his interest in separating out ‘artistic’ or cultural forms of expression as opposed to those generated by the body's own internal forces. His own archive contained many images from the history of art, including Sandro Bottocelli's Madonna del Magnificat , among others ( Vanone, Lorusso, and Venturini, 2016 ). Like Charcot, he wanted to understand how mental, even spiritual, states could lead to powerful bodily gestures and movements.…”
Section: Signs Symptoms and Cinemamentioning
confidence: 99%
“…As Federico Vanone, Lorenzo Lorusso, and Simone Venturini have pointed out, Neri's mode of working demonstrated his interest in separating out ‘artistic’ or cultural forms of expression as opposed to those generated by the body's own internal forces. His own archive contained many images from the history of art, including Sandro Bottocelli's Madonna del Magnificat , among others ( Vanone, Lorusso, and Venturini, 2016 ). Like Charcot, he wanted to understand how mental, even spiritual, states could lead to powerful bodily gestures and movements.…”
Section: Signs Symptoms and Cinemamentioning
confidence: 99%
“…For example, the Italian neurologist Vincenzo Neri filmed patients in his clinic and then revisited the material through techniques of frame enlargement and decomposition of the film into units. Evolving what Vanone, Lorusso, and Venturini name a ‘clinical semiotics’ through the use of film, Neri scrutinised the negative stock to isolate the moment in which the patient's pathology emerged ( Vanone, Lorusso, and Venturini, 2016 ). Neri's embrace of film, influenced by the chronophotographic techniques of Etienne-Jules Marey, demonstrated that a filmed body acquired meaning through a complicated system of interpretation.…”
mentioning
confidence: 99%